The complete mitochondrial genome of Metasepia tullbergi (Cephalopoda: Sepiidae) - Hung-Tai Lee; Cheng-Hsin Liao; Chang-Wen Huang; Chia-Huan Ma; Te-Hua Hsu (Mitochondrial DNA. Part B. Resources, 2021)
The first complete mitochondrial genome of Metasepia tullbergi has been characterized in this study. The circular mitogenome is 16182 bp in length and comprises 13 protein-coding genes (PCGs), 22 transfer RNA genes, and two ribosomal RNA genes. The organization of these genes is highly consistent with that of other Sepiidae. The overall base composition of mitogenome is 39.20% A, 36.07% T, 8.98% G, and 15.75% C, with 75.27% AT. Phylogenetic analysis further suggests that M. tullbergi is placed within the Sepiidae and is closely related to Sepia latimanus and S. apama.